Low Consumer Social Responsibility Increases Willingness to Buy from Large vs. Small Companies - Uzdavinyte, Elze; Kaminskiene, Zivile (Organizations and Markets in Emerging Economies, 2023)
Previous research mainly concentrated on the link between the company size and consumer perceptions related to corporate social responsibility (CSR). Here we aim to extend the previous findings to the context of the consumer’s individual trait of social responsibility. Building on signaling theory, we analyze such signals as company size and demonstrate that consumers have a decreased willingness to buy a product originating from a large company as compared to a small company. However, the effect flips for consumers with low social responsibility as they show a higher willingness to buy large company products. We contribute to signaling theory by showing that consumer traits such as consumer social responsibility can play an important role in the effectiveness of the signal. In addition, these findings contribute to consumer social responsibility research as well as consumer behavior literature by showing that the company size effect is moderated by consumer social responsibility. Theoretical and managerial implications are discussed together with directions for future research.